Design and Simulation of Plastic Injection Moulding Process - Wong, Choon Tat; Sulaiman, Shamsuddin; Ismail, Napsiah; Salem Hamouda, Abdel Magid (Universiti Putra Malaysia Press, 2004)
This paper presents the design of plastic injection mould for producing a plastic product. The plastic part was designed into two different types of product, but in the same usage function. One part is using clip function and another part is using tick function. In the computer-aided design (CAD), two plastic parts were drawn in 3 dimension (3D) view by using Pro-Engineer (Pro-E) parametric software. In the computer-aided manufacturing (CAM), Pro-Manufacturing from Pro-E parametric software was used to develop the machining program. For mould design, the product was designed into two changeable inserts to produce two different types of plastic product in one mould base. Before proceeding to injection machine and mould design, this part was analysed and simulated by using Mold Flow or Part Advisor software. From the analysis and simulation we can define the most suitable injection location, material temperature and pressure for injection. The predicted weld lines and air trap were also found and analysed.